Bismuth film electrodes for adsorptive stripping voltammetrypreparation, properties and analytical application - Królicka, Agnieszka; Bobrowski, Andrzej (Univerzita Pardubice, 2005)
The properties of the bismuth film electrode (BiFE) designed for adsorptive stripping voltammetry were examined by electrochemical and microscopic techniques (optical microscopy, SEM-EDX, AFM). The BiFE was prepared by exsitu electrodeposition of a Bi film onto a glassy carbon disk support. The composition of the plating solution, the influence of accumulation potential, the stability of bismuth coatingas well as the memory effect were investigated. The analytical usefulness of the BiFE obtained by the proposed procedurefor adsorptive stripping voltammetric measurement of cobalt traces in a solution of 1x10-4 M DMG and 0.1 M ammoniabuffer was assessed. It was found that the plating solution containing 0.02 M Bi(NO3)3, 1 M HCl and 0.5 M LiBr combined with a plating potential of -0.28 V and c.a. 35 s plating time ensure the finest quality bismuth film. The elctrode-to-electrode reproducibility of the described plating procedure evaluated in terms of the relative standard deviation (RSD) was equal to 12%. The repeatability of the cobalt response for 30 subsequent adsorptive stripping measurements of the same BiFE amounted to RSD = 6%. The performance of the BIFE for trace cobalt and nickel analysis in geological samples is presented.
Keywords: adsorptivní rozpouštěcí voltametrie; BiFE; vlastnosti; aplikace; kovy; stopová koncentrace; stanovení